The concept of ‘Spin Doctoring’: weaving the net in the information age - Cala Siria, Mª de los Reyes (Estudios sobre el Mensaje Periodístico, 2015)
During the celebration of the electoral debate between Ronald Reagan and Walter Mondale, the 20th october 1984, experts in communication surrounding the candidates acquired visibility to journalists. A day later, the New York Times, in its editorial, defined them with the term of spin doctor. Since then, this concept passed to be analysed in the academic world. In general terms, this activity is understood as spinning a story to the most positive point of view. In this article, according to professor José Luis Dader, I defend a notion based on weaving net to journalists in a subtly and permanent way, without using imperatives elements. Thus, it appeals to a more democratic way of understanding the relationship between the spin doctor and his influence on journalists.
Keywords: political communication; spin doctor; journalism; persuasion; weaving the net.